The Analysis Of The Relationship Between Work-Life Balance, Work Environment, And Employee Engagement On Job Satisfaction At UPT PLN Malang - Dwi Danesty Deccasari Danesty; Rina Irawati Rina (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This causal quantitative research analyzes the influence of Employee Engagement , Work Environment , and Work Life Balance on Job Satisfaction in the employee population of UPT PLN Malang , with 89 respondents using purposive sampling , and analyzed using PLS-SEM. The results show that Employee Engagement (path coefficient 0.540, P-value 0.000) and Work Environment (path coefficient 0.360, P-value 0.000) have a positive and significant effect on Job Satisfaction , explaining 78.9% of the variation ( R-square = 0.789). However, Work Life Balance (path coefficient 0.045, P-value 0.252) does not have a significant effect. Further research recommendations are to explore mediating/moderating variables for Work Life Balance and use a qualitative approach for a deeper understanding.